Impact of laboratory facilities access in Kwara State, Nigeria on student performance in upper basic schools - Florence Omosholape Abidoye; Odunole Bilikis Adedeji (Universitas Wiralodra, 2022)
The low learning outcomes of students caused by the underutilization of science laboratory facilities in some Kwara State Upper Basic Schools need to reveal. Thus, this research aimed 1) to analyze the effect of science laboratory utilization by the teachers and their experience on the students' learning outcomes, 2) to analyze the effect of science laboratory utilization by male and female teachers on the students learning outcomes, and 3) to analyze the effect of science laboratory utilization by experienced teachers to the students' learning outcomes. It is ex post facto research with multiple linear regression analysis due to its two independent variables. This research took both public and private upper primary school teachers in Kwara State, Nigeria, as the population. Forty-seven Public and Private Upper Basic Schools in all parts of the state are taken as samples randomly in this research. There were 100 basic science teachers taken as respondents. This research reported that 1) teachers’ utilization of science laboratory based on gender and experience in teaching science simultaneously influence students' learning outcomes with value Sig. 0,00 < 0,05, 2) the utilization of the science laboratory by the male and female teachers did not significantly influence the students' learning outcomes, with value Sig. Equal variances assumed 0,017 < 0,05, and 3) the utilization of a science laboratory by experienced teachers in teaching basic science significantly influenced one student’s learning outcomes.